Commercial nonindustrial production of pastries and ice cream in Naples, Italy: results from the inspection of 34 food businesses during a 2-year surveillance study (Italian Journal of Public Health, 2010)
Background: Ice cream and cream-based pastries are an excellent media for the growth of pathogenicmicroorganisms. Foods that are prepared without due respect to the rules of food hygiene can carrymicroorganisms and/or toxins and could be responsible of toxinfections. The main objective of this study wasto obtain an overall picture of the hygiene/sanitation conditions found in businesses that produce hand-madepastries and/or ice cream in Naples, Italy.Methods: We inspected 34 businesses to assess the following aspects: hygiene/sanitation conditions of thework area and equipment, implementation of good food hygiene principles, evaluation of HACCP plans,licensing/authorization, quality control and sampling protocols, as well as systems for ensuring foodtraceability. In 28 of the businesses, samples (environment, foods, workers) were collected formicrobiological analysis.Results: Sanctions were issued for nonconformities in 8 businesses (23.5%), and 25 businesses (73.5%)received warnings with orders to correct minor nonconformities (inadequate documentation of compliancewith current regulations, incorrect implementation of the quality-control protocol) within specified timeperiods. Microbiological analyses revealed irregularities in 24/28 businesses (85.7%), and 138 of the 280samples collected displayed contamination levels exceeding the limits adopted for this study (49.3%). Inparticular, 80% of the surfaces sampled and 23.8% of the hand swabs collected were shown to becontaminated. All food samples collected met the process-hygiene and food-safety standards prescribed bythe European Community. Results obtained were statistically significant (p < 0.05).Conclusions: Our experience of food safety surveillance system indicates that Neapolitan food businessoperators involved in the production of hand-made ice cream or pastries do not fully understand theimportance of the general preventive measures such as Good Hygienic Practices, Good ManufacturingPractice and Hazard Analysis Critical Control Point Codex requirements for providing consumers with safe,high-quality food products.
Keywords: Ice cream; pastries; food safety